Circadian photoreception: The impact of light on human circadian rhythms - Zeitzer, Jamie M.; Lok, Renske (Circadian and Visual Neuroscience, 2022)
Light is the preeminent external influence in determining the position of the internal circadian clock relative to the outside world. In this chapter, we discuss the different parameters of light that impact how it influences the human circadian clock. We detail how the timing (phase), intensity, duration and temporal structure, and spectral composition all can modulate the impact of light on both the timing of the circadian clock as well as its amplitude. The neurobiological underpinnings of the system are briefly discussed in the context of understanding how light can evoke its observed effects on the circadian clock.